Comprometimento organizacional em diferentes setores produtivos: analisando as dimensões do construto em distintos contextos de precarização do trabalho - Furtado, Valéria Araújo (2020)
Organizational Commitment represents one of the most investigated constructs in order to understand the bonds that the worker builds with the organization. The fragmentation of concepts and the scarcity of national empirical studies that search it in its three dimensions mark its development. In order to contribute to the expansion of research in the area and the reduction of conceptual problems, this work proposes to study the referred construct in its three bases (Affective, Normative and Continuance), with emphasis on the “side bets” established between individual / organization. The objective here is to analyze the phenomenon from the perspective of the worker, exploring its dimensions in different productive sectors and in different contexts of precarious work. The specific objectives are (a) to map the meanings and concepts about Organizational Commitment in different workers' perspectives, (b) to identify bond profiles, (c) to identify and develop a comparative analysis between the different dimensions of the construct from the perspective of each subject, d) to analyze how the “side bets” occur between workers who experience different contexts of precarious work and (e) explore the concepts of precarious work in different perspectives of workers. It is a qualitative, descriptive and exploratory research that was carried out through semi-structured interviews with sixteen subjects from three different categories of productive sectors: public servants, industrialists and application drivers. Data analysis was done through content analysis and definition of codes with the assistance of qualitative research software ATLAS.ti7. The main results revealed that the three categories of workers studied attribute to Organizational Commitment meanings linked to positive aspects, which predominate the congruence between individual and organizational values, motivation, pleasure and involvement with the institution. It was also found that in the three groups of workers, Affective Commitment was shown to be more representative, thus showing the emotional attachment, pride and feeling of belonging of these individuals to the organization. Normative and Continuance Commitment were presented in a balanced way for each group, but with specificities. These results confirm the relevance of the multidimensional proposal for Organizational Commitment from different mindsets. However, it was noticed that, even though the individuals surveyed are in different contexts of precariousness, the groups have similar perceptions about the rewards they receive due to work (side bets) and that these are linked to economic, social factors, job opportunities. career development, flexibility, recognition, autonomy and learning. Finally, it was identified that precarious elements of the work were evidenced mainly by public servants and application drivers and that they are related to inadequate environmental conditions such as deficient physical structure and scarcity of resources for the performance of the activity, as well as to public security problems , respectively. The main collaboration of this research was to favor a better outline in the understanding of the link of Organizational Commitment in different contexts of precarious work; as well as helping to strengthen the construct's multidimensional approach.